BI7DRR and CPI Inflation Impacts on IDX30 Index Fund Performance with TER Moderation - Embun Prowanta; Amelia Sintama (Cita konsultindo, 2026)
In this study, the author aims to analyze the effect of interest rates and inflation on the performance of conventional index mutual funds (IDX30) with the Tracking Error Ratio (TER) as a moderating variable. The study was conducted at PT BNI Asset Management, one of the leading investment management companies in Indonesia registered with the Financial Services Authority (OJK), using data obtained from 2020 to 2024. The research method employed is a quantitative approach with secondary data analysis using Eviews. The findings of this study indicate that interest rates have a negative and significant effect on the performance of index mutual funds, inflation has a negative and significant effect on the performance of index mutual funds, the tracking error ratio is able to moderate the effect of interest rates on the performance of index mutual funds by weakening the negative relationship between them, and the tracking error ratio is also able to moderate the effect of inflation on the performance of index mutual funds by weakening the negative relationship between them